Islam and Modern Conflict Resolution (Islah) in Media: Case of Controversial Thread On Flex Menstrual Disc - Nizami, Auliya Ghazna (TSAQAFAH, 2025)
The concept of human peace, traditionally explored in the context of physical or political conflicts, has gained relevance in digital spaces where human interactions increasingly occur. This article examines how peaceful narratives can emerge within controversial discussions online, focusing on a specific case: the debate around the use of the flex menstrual disc. Using Netnography as the primary method, this study observes netizen interactions within a polarized thread, highlighting how, despite differing opinions, some participants contribute to a constructive and peaceful dialogue. Supported by theories such as Nonviolent Communication and Conflict Resolution, the research seeks to identify language patterns and behaviors that foster peace, even in contentious digital environments. The results of this study are to demonstrate that peaceful engagement is possible in online discussions, offering insights into how human peace can be maintained and encouraged in digital interaction spaces.